Strategi Pemasaran “Creative Bell” Desain Grafis dalam Program Desain Produk Gratis pada UMKM - Rio Mahabelly Betrand; Suwarsi, Sri; Muhamad Taufik Permana, Rezi (UNISBA Press, 2024)
Abstract. Creative Bell is a graphic design service company that was founded in 2021. This company offers various graphic design services such as logos, posters, brochures, business cards, etc. at affordable prices and professional quality. By using the latest technology and an experienced creative team,